Analysis for public decisions - Quade, Edward S. (1975)
This volume focuses on analytic methods as alternatives to traditional public policy decision-making methods.Covers a broad spectrum of analytic aids to decision making; focuses on the needs of the users rather than the interests of analysts; demonstrates that analysis is not limited to questions that can be quantified; and provides information -- both practical and theoretical -- on questions that are important to those who need analytical help and to those responsible for sponsoring, evaluating, and implementing the analyses of others.